Model Collaborative Governance pada Nagari Rancak di Provinsi Sumatera Barat - Syamsurizaldi Syamsurizaldi; Annisa Aulia Putri; Suherdian Antoni (Jurnal Pembangunan Nagari, 2019)
Nagari Rancak is the name for the nagari who won achievements in the village race with the level of West Sumatra Province as an instrument to evaluate the development of the village (nagari) in accordance with Minister of Home Affairs Regulation No. 81 of 2015. Nagari rancak who has achieved various achievements is assumed to have implemented Nagari in accordance with the principles of good local governance and collaborative governance. Based on these phenomena, the objectives of this study are: (1) to describe the profile of the nagari rancak after the enactment of Law Number 6 of 2014 concerning Villages in West Sumatra Province; (2) identify stakeholder actors in the nagari rancak in West Sumatra Province; (3) describe the interaction of stakeholders in collaborative governance in the nagari in West Sumatra Province, and (4) describe the success of collaborative governance in nagari rancak in West Sumatra Province. This study included the type of qualitative research with descriptive analysis. Data sources are stakeholders in the administration of the nagari government as informants and the nagari assessment team is ambitious as triangulation. Data collection through interviews, documentation and observation. The research location was in 9 (nine) nagari which won 1st, 2nd and 3rd place in the provincial nagari competition in 2015, 2106 and 2017. The results of the study found that: (1) Ambiguous Nagari has varied economic potential, has many achievements and variations actors who collaborate in organizing the nagari government. (2) Governance actors collaborating with the nagari government starting from the nagari, sub-district, district, provincial and national levels. The realization of this collaboration was greatly influenced by the existence of self-disclosure and initiatives from Wali Nagari and Alat Nagari. (3) Collaborative actor governance occurs at every stage of the administration of nagari governance, namely planning, budgeting, implementing, monitoring and accountability. However, the most intensive actor interaction at the planning and implementation stages of programs and activities at the nagari level. (6) Collaborative success can be seen from eight indicators according to Goldsmith and Kettl (2009), namely networked structure, commitment to common purpose, trust among participants, governance, access to authority, distributive accountability, informant sharing, and access to resources.